The Style of Letters and Meaning: Integration of Arabic Literary Aesthetics in the Teaching of Kitab Kuning in Pesantren - M. Fathor Rohman; Isna Finurika; M. Chotibuddin (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2026)
Learning the kitab kuning (classical Islamic texts) has so far tended to focus on grammatical and legalistic aspects, while aesthetic elements such as rhythm, metaphor, and linguistic style have not been fully explored as pedagogical tools. This study employs a qualitative approach through a literature review of classical texts such as Alfiyyah Ibn Mālik, Syarḥ Imrīṭī, and Fath al-Muʾīn, which are analyzed from the perspectives of Arabic stylistics and balāghah (rhetoric). The findings indicate that integrating a literary approach in the study of kitab kuning enhances students’ understanding of the structure and meaning of the texts, cultivates linguistic sensitivity, and fosters an appreciation of aesthetic and cultural values. This article recommends transforming pesantren learning methods by systematically incorporating classical Arabic literary approaches to enrich the dimensions of comprehension, internalization, and interpretation of turāth (heritage) texts.